Contemporary methods of therapy and follow-up of neuroendocrine tumours of the gastrointestinal tract and the pancreas - Gut, Paweł; Fischbach, Jakub; Kamiński, Grzegorz; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2012)
The growing interest in neuroendocrine tumours is due to the dynamic growth of detection of this type of cancer. Neuroendocrine tumours (neuroendocrine neoplasms – NENs / neuroendocrine tumours – NETs) derive from glands, groups of endocrine cells and diffuse neuroendocrine system cells. Mainly they derive from the gastrointestinal tract (gastroenteropancreatic-neuroendocrine tumours – GEP-NETs). Currently the modified WHO classification from 2010 is widely used. An important element in the choice of treatment is histological maturity based on mitotic activity and on assessment of proliferation activity (Ki-67). The treatment of choice is surgery. In most cases, complete surgical removal is impossible because of the advanced staging at the time of diagnosis. In well-differentiated neoplasms where the expression of somatostatin receptors is expected, patients are qualified for somatostatin analogues therapy. Poorly differentiated lesions are qualified for chemotherapy. In the guidelines of ENETS (European Neuroendocrine Tumor Society) from 2007 the rules concerning monitoring depending on the WHO classification were specified.